Programming Regulation and Strategic Planning in the Health Care Sector - G. V. Muliar (Bulletin of Kharkiv National University of Internal Affairs)
The article deals with the legal characteristics of forecasting and strategic planning in the health care sector through program regulatory acts, their rationality and effectiveness of application, revealing the main characteristics and regularities of such regulation and the place in the system of national legislation, as well as identifying problems and shortcomings of program regulation of the health care sector in Ukraine, the formulation of propositions to eliminate the relevant complications in domestic practice.